Ultra-wide bandwidth time-hopping spread-spectrum impulse radio for wireless multiple-access communications. - Win, M.Z (IEEE Transactions on communications)
Attractive features of time-hopping spread-spectrum multiple-access systems employing impulse signal technology are outlined, and emerging design issues are described. Performance of such communications systems in terms of achievable transmission rate and multiple-access capability are estimated for both analog and digital data modulation formats under ideal multiple-access channel conditions